An estimate of lucid dreaming incidence - Gackenbach, Jayne (My University, 1984)
Prevalence, how many people have ever had at least one lucid dream; and frequency, how often does an individual experience these dreams are two ways of conceptualizing lucid dreaming incidence. Seven surveys have attempted to ascertain the prevalence of lucid dreaming in both student (Palmer, 1979; LaBerge, in press; Gackenbach, Rokes, Sachau & Synder, 1984) and adult (Palmer, 1979; Kohr, 1980; Blackmore, in press; Gackenbach, 1978; Gackenbach, Curren, LaBerge, Davidson & Maxwell, 1983) samples. Among the latter estimates of having had at least one lucid dream range from 100% (Gackenbach et al., 1983) to 47% (Blackmore, in press). Both sample characteristic considerations and understanding of the concept clarify the picture. Kohr (1980), Gackenbach (1978) and Gackenbach et al. (1983) were all dealing with highly motivated adult samples. That is, people who have an unusually high interest in dreaming and/or lucid dreaming. Thus their estimates tend to run high (Kohr, 70%; Gackenbach, 76%; Gackenbach et al., 100%). In the Palmer (1979) and Blackmore (in press) surveys, adults were randomly chosen from the telephone directory in the case of the former and from the electoral register in the case of the latter. Consequently, their estimates are considerably more conservative: Palmer, 55% and Blackmore, 47%. However, there is no indication that they attempted to verify that their respondents understood the concept.
Keywords: dreams; lucid dreaming